Determinação social da saúde e sofrimento psíquico na universidade: uma pesquisa com estudantes do Instituto de Ciências Matemáticas e de Computação (ICMC) do campus da USP de São Carlos - Silva, Emanuela Pap da (Universidade Federal de São Carlos, 2021)
Questions about psychic suffering are often associated with the university environment, and they represent challenges that require institutional policies to be sought. It is crucial to understand how psychic suffering manifests in different university contexts, to know which are its actual dimensions and determinants. Through a critical perspective, knowledge about psychic suffering can allow the interpretation of the health-disease process of organizing social life, work, and social reproduction. This study intends to identify the prevalence of psychic suffering and its associations based on the understanding of social determination in health among undergraduate and graduate students at USP São Carlos, at one of its teaching units, the Institute of Mathematical and Computer Sciences (ICMC). The research was based on an exploratory epidemiological population, observational, cross-sectional, institutional studies with a critical analysis of 310 undergraduate students and 122 graduate students. The data collection was carried out electronically between September and November 2020, through a self-administered questionnaire composed of a socio-demographic inventory and on health issues and the instrumental Self-Reporting Questionnaire (SRQ-20), which signals the presence of psychological suffering by screening for Common Mental Disorders (CMDs). Data was exported to the RStudio program (R CORE TEAM, 2020) and the Stata program version 14 (College Station, Texas, USA) to analyze distributions and associations. Among undergraduate students, the results showed a general prevalence of CMDs was 72.9%. There was an association with family per capita income, income variation from the period before the pandemic caused by COVI-19 and the moment of research, being a cisgender woman, LGBTQIA+ sexual orientation, reporting difficulty in staying at the University, being followed up with a mental health professional and making use of psychiatric medication. In the adjusted analysis, we found an association and odds ratio between positive screening for CMDs and being a cisgender woman (OR = 2.69), reporting difficulties in staying at the University (OR = 3.45) and being monitored by a mental health professional (OR = 3.74). For graduate students, the general prevalence of CMDs was 72.1%. We found an association with family per capita income, reporting difficulty staying at the University, being monitored by a Mental Health professional, and using psychiatric medication. In the adjusted analysis, we found an association and odds ratio between positive screening for CMDs and difficulty staying at the University (OR = 10.3). The prevalence of psychic suffering was high in both groups. These findings can serve as the basis for the development and improvement of public policies for Student Assistance in the context of Collective Health and the Unified Health System. Among the recommendations is the strengthening of the national assistance policy student, with the expansion of coverage to graduate students, strengthening and creating actions and diversity policies that combat prejudice and discrimination at the national and local levels. It is necessary to consider the transformation of the university environment as well as beyond its limits, considering that what is lived at the university is also a reflection of life outside it.
Social determination of health and psychic suffering at the university: a survey with students from the Instituto de Ciências Matemáticas e de Computação (ICMC) at USP campus of São Carlos
Keywords: Saúde mental; Determinantes sociais da saúde; Universidades; Mental health; Social determinants of health; Universities; CIENCIAS SOCIAIS APLICADAS; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA